A typology of esport players - Hedlund, D. P. (Journal of Global Sport Management, 2021)
In recent years, esports have grown from a small number of local gaming activities undertaken by a few recreational participants to a multi-billion dollar industry with professional leagues, franchises, teams and players. While the industry has grown, our collective understanding of some of the most fundamental questions such as who plays esports and why, have received scant attention from academics. In an effort to further understand, profile and categorize players, the purpose of this research is to create a typology of esports players and to cross-validate previous research findings. Using hierarchical and k-clustering techniques, six psychographic factors (socialization, positive affect, competition, fantasy/escape, coping, pass/waste time) and additional demographic and behavioral characteristics are used to create a typology of esports players. Based on a large, diverse and international sample of respondents (n = 1165), five types of players, including (1) Competitive, (2) Casual, (3) Casual-Social, (4) Casual-Fun, and (5) Casual-Competitive esports players, are identified. In-depth examination and discussion of the five types of players are provided. The implications of this research suggest the importance of considering demographic, psychographic and behavioral characteristics when attempting to identify, understand and classify different types of esports players.